2019
DOI: 10.1259/bjr.20190840
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in diagnostic imaging: impact on the radiography profession

Abstract: The arrival of artificially intelligent systems into the domain of medical imaging has focused attention and sparked much debate on the role and responsibilities of the radiologist. However, discussion about the impact of such technology on the radiographer role is lacking. This paper discusses the potential impact of artificial intelligence (AI) on the radiography profession by assessing current workflow and cross-mapping potential areas of AI automation such as procedure planning, image acquisition and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 55 publications
1
92
0
4
Order By: Relevance
“…Adaptability will be a vital standpoint for those navigating immediate pandemic-related challenges and also ongoing professional revolutions such as automation and AI. 15,16 Using more than one clinical education department and elective placements are recognised ways to promote student adaptability through exposure to different ideas, practices and team cultures. 5,17 Work by the King's Fund suggests that incorporating theory and practice of compassionate leadership into undergraduate curricula, and even earlier at NHS cadet scheme level, 18 is also likely to contribute significant benefits to the individual and collective response to a health service crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptability will be a vital standpoint for those navigating immediate pandemic-related challenges and also ongoing professional revolutions such as automation and AI. 15,16 Using more than one clinical education department and elective placements are recognised ways to promote student adaptability through exposure to different ideas, practices and team cultures. 5,17 Work by the King's Fund suggests that incorporating theory and practice of compassionate leadership into undergraduate curricula, and even earlier at NHS cadet scheme level, 18 is also likely to contribute significant benefits to the individual and collective response to a health service crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the medical community must anticipate the potential unknowns and professional requirements of this technology to ensure effective, continuous and safe incorporation into diagnostic imaging practice [ 1 , 10 , 13 ]. This has initiated arguments about the roles and responsibilities of imaging professionals who will use this technology, particularly, radiographers and radiologists [ 13 , 14 ]. Lewis and colleagues [ 4 ] reported that some radiographers may have a scary or exciting perception about AI, and these could be heightened by the thought of having an ‘AI work colleague’ in the radiology department.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is the potential for AI to contribute to and help in the automated examinations of referrals, checking the clinical indications and confirming the patient’s identification via an interface with the Electronic Health Record. AI technologies can also assist in imaging modality techniques and processes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%